2018
DOI: 10.7554/elife.34836
|View full text |Cite
|
Sign up to set email alerts
|

Boosting ATM activity alleviates aging and extends lifespan in a mouse model of progeria

Abstract: DNA damage accumulates with age (Lombard et al., 2005). However, whether and how robust DNA repair machinery promotes longevity is elusive. Here, we demonstrate that ATM-centered DNA damage response (DDR) progressively declines with senescence and age, while low dose of chloroquine (CQ) activates ATM, promotes DNA damage clearance, rescues age-related metabolic shift, and prolongs replicative lifespan. Molecularly, ATM phosphorylates SIRT6 deacetylase and thus prevents MDM2-mediated ubiquitination and proteaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 86 publications
2
45
0
Order By: Relevance
“…During senescence, DDR deficiencies are accompanied by changes in glucose metabolism characterized by impaired mitochondrial respiration and increased glycolysis, producing more lactate [66]. Activation of ATM via a low dose of chloroquine, an autophagy inhibitor that is used to treat malaria, results not only in improved DNA damage clearance, but also rescue of age-related metabolic changes (inhibition of glycolysis) and prolonged cellular replicative capacity [67]. Mechanistically, ATM phosphorylates SIRT6, which leads to protein stabilization and enhanced function.…”
Section: The Progeria Cell and Energymentioning
confidence: 99%
See 1 more Smart Citation
“…During senescence, DDR deficiencies are accompanied by changes in glucose metabolism characterized by impaired mitochondrial respiration and increased glycolysis, producing more lactate [66]. Activation of ATM via a low dose of chloroquine, an autophagy inhibitor that is used to treat malaria, results not only in improved DNA damage clearance, but also rescue of age-related metabolic changes (inhibition of glycolysis) and prolonged cellular replicative capacity [67]. Mechanistically, ATM phosphorylates SIRT6, which leads to protein stabilization and enhanced function.…”
Section: The Progeria Cell and Energymentioning
confidence: 99%
“…Studies in vivo show that extra copies of Sirt6 in ATM-deficient mice restore metabolic homeostasis and extend lifespan. Given that progeria cells exhibit deficiencies in ATM and SIRT6 function, the authors investigated the possibility of using chloroquine to improve aging phenotypes in vitro and in vivo [67]. Relevantly, chloroquine treatment of progeria cells activated Atm, stabilized Sirt6, reduced DNA damage, inhibited glycolysis, and ameliorated senescence.…”
Section: The Progeria Cell and Energymentioning
confidence: 99%
“…19,41 Furthermore, ATM deficiency has been shown to enhance innate immune signaling. [43][44][45][46] Additionally, we have demonstrated that the ATM-recruitment domain (∆703-754 or ∆ATM) of NBS1 is critical for attenuating cGAS binding to micronuclei in response to 6-thio-dG ( Figs. 3B-C).…”
Section: Atm-mediated Nbs1 Stabilization On Chromatin Fragments Attenmentioning
confidence: 97%
“…ATM‐deficient mice display many of the pleiotropic symptoms found in AT patients and also have shortened life expectancies (Barlow et al , 1996). By contrast, an increase in ATM activity alleviates aging and extends longevity by phosphorylating and stabilizing the pro‐longevity enzyme SIRTUIN 6 in mouse (Qian et al , 2018). It was recently reported that DSBs caused by the inducible expression of a restriction endonuclease Sac I led to premature aging phenotypes, suggesting that DSBs alone were sufficient to accelerate the aging process, at least in some organs (White et al , 2015).…”
Section: Introductionmentioning
confidence: 99%